1970
DOI: 10.3126/kumj.v8i2.3571
|View full text |Cite
|
Sign up to set email alerts
|

An ultrasonographic evaluation of solitary muscular and soft tissue cysticercosis

Abstract: Background: Cysticercosis in humans is infection with the larval form (cysticercus cellulosae) of the pork tapeworm T. solium. Encystment of larvae can occur in almost any tissue. The location of cysts in order of frequency is the central nervous system, subcutaneous tissue and striated muscle, vitreous humour of the eye and, rarely, other tissues. High resolution ultrasound can be used in the diagnosis of muscular and soft tissue cysticercosis. Objective: The aim of this study is to evaluate the ultrasonograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 8 publications
1
14
0
Order By: Relevance
“…Commonly, patients present with multiple lesions such as cysts of different sizes associated with varying degrees of host response, nodular enhancing lesions and residual calcifications sometimes accompanied by perilesional edema [5]. The cysts are ovoid and white to opalescent, rarely exceeding 1.5 cm, and contain an invaginated scolex with hooklets that are bathed in clear cyst fluid [6].…”
Section: Discussionmentioning
confidence: 99%
“…Commonly, patients present with multiple lesions such as cysts of different sizes associated with varying degrees of host response, nodular enhancing lesions and residual calcifications sometimes accompanied by perilesional edema [5]. The cysts are ovoid and white to opalescent, rarely exceeding 1.5 cm, and contain an invaginated scolex with hooklets that are bathed in clear cyst fluid [6].…”
Section: Discussionmentioning
confidence: 99%
“…Isolated head and neck muscle cysticercosis is an extremely unusual site of involvement and extensive search of literature revealed that isolated temporalis muscle cysticercosis is even rarer [11]. Diagnosis of isolated muscular cysticercosis is a very perplexing problem due to their rarity and nonspecific manifestations and often present as a diagnostic dilemma to the clinician [12]. Cysticercosis may remain asymptomatic for variable period of time or may present with severe local symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Cysticercosis may remain asymptomatic for variable period of time or may present with severe local symptoms. Various types of local clinical manifestations such as myalgic, myopathic, nodular or mass like and the rare pseudohypertrophy have been described in the literature [12]. The various differential diagnosis may include lipoma, fibroma, neurofibroma or intermuscular abscess and it is difficult to diagnose this condition solely on a clinical basis [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cysticercosis is an infection caused in humans by the larval form of the pork tapeworm T. solium (i.e, Cysticercus cellulosae) [2]. T. solium exists worldwide but is most prevalent in Latin America, sub-Saharan Africa, China, southern and Southeast Asia, and Eastern Europe [3]. The pork tapeworm eggs, when ingested through the contaminated food, water or dirty hands leads to the parasitic infestation [4].…”
Section: Introductionmentioning
confidence: 99%